A emenda de Séneca - Machado de Assis e a forma do conto - Baptista, Abel Barros (Teresa, 2005)
Beginning with the short story “O empréstimo”, from Papéis avulsos, this essay analyzes the form of Machado de Assis’ short stories in their relationship to the problem of interpretation: the short form outlines the interpretation of a moment, a happening, a scene or an episode, and these, in turn, have a global quality through this very interpretation. The problem is then solved, but precariously and provisionally. In this resolution of the problem the figure of authority o f the narrator plays a decisive role, and this study analyzes three examples of the narrator in “O espelho”, "Primas de Sapucaia” and “A causa secreta”